INDONESIAN FISHERIES PHENOMENA: Development, Enhancement and Management - Indah Susilowati (JOURNAL OF COASTAL DEVELOPMENT, 2000)
Indonesia has a great endeavor in fisheries resources. However, most of the resources remain underutilized in some extents. At the same time, resources disparity is occurred in Indonesian fisheries. Tight competition among the resource users happen in fisheries with dense population. In such situation, thereafter, tragedy of common phenomena will happen. Managing fisheries resource in the condition which constitutes thousands of islands like Indonesia is not an easy task and should be quit costly in expenses. One of strategies that require less in cost and could promise a better achievement is through reviving the potency which belongs to the community (such as traditions, customs, beliefs, etc.) and with empowering community to manage the fisheries resource.